The Internet as a source of reproductive health information among adolescent girls in an urban city in Nigeria - Nwagwu Williams E (BMC, 2007)
Abstract Background There exists some research evidence regarding how adolescents utilize the Internet for health information seeking purposes. The purpose of this study is to understand how in-school and out-of-school adolescent girls in Owerri, Nigeria use online resources to meet their reproductive health information needs. The result could be considered very crucial in assessing the potential role of the Internet in providing health information to adolescent girls in a typical Nigerian urban city. Methods A questionnaire was used to collect data from 1011 adolescent girls in selected secondary schools in the communities, and also from 134 out-of-school girls selected from the same communities. Results More than 73% of the girls reported having ever used the Internet; more than 74% and 68% of them being in-school and out-of-school respectively. The in-school girls (43.9%) reported having home access more than the out-of-school (5.6%) although the out-of-school have used the Internet for finding reproductive and related information more than the in-school. While parents (66.22%) and teachers (56.15%) are the two sources most used to the in-school girls, friends (63.18%) and the Internet (55.19%) were reported by the out-of-school youth as the two most used sources of information to them. Conclusion The Internet is not a first choice of source of reproductive health information for both the in-school and out-of-school adolescent girls in Owerri, Nigeria. The source is however, more commonly used by the out-of-school than the in-school, but the in-school have a more favorable assessment of the quality of information they obtain from the Internet.